Sweeping the city: infrastructure, informality, and the politics of maintenance. Issue 4 (3rd September 2021) - Gordon, Constance; Byron, Kyle
ABSTRACT: Uneven development in many North American cities has given rise to an increasing number of homeless encampments as residents seek shelter, sanitation, and other basic needs outside of formally recognized networks. In gentrifying cities, these informal infrastructures are also subject to the recurring violence of sweeps, wherein states remove, seize, or destroy life-sustaining necessities to decrease their visibility and designate space for other uses. The sweep is both a strategy of governance and a viscerally felt phenomenon in which infrastructural networks become terrains of contestation. In this article, we examine the cultural politics of sweeps through the analytic of maintenance. Drawing on examples from Toronto, Ontario, Canada and San Francisco, California, United States, we argue that sweeps are mechanisms of policing that often operate through the apparently benign work of routine maintenance, which in turn iteratively organizes belonging and exclusion in cities. These dynamics have thereby become important sites for infrastructural struggle. With our analysis, we join scholars in the study of infrastructure taking a critical stance toward processes of maintenance and repair, asking questions about what is being maintained, for whom, and toward what end.